Energy Adaptive Approach for Node Inclusion and Exclusion in Dynamic Clustered WSN (International Journal of Engineering and Computer Science, 2014)
A sensor network is an energy effective communication network organized under specific network architecture. One of such structured architecture followed by sensor network is clustered network. The communication in such cluster network is one of the effective challenges because of different kind of responsibility to different roles of a node. This communication becomes more challenging when the network is dynamic and any node can participate in communication. The proposed approach improves the effectiveness of communication in structured network while including or excluding a new node over the network. In this paper, a two level analysis approach is defined to perform the dynamic operations over the network.